THE INFLUENCE OF STEM CELLS ON EARLY STAGES OF THE GRAFT IMMUNITY - V. A. Lyashenko; D. V. Goldshtein; A. A. Rzhaninova (Медицинская иммунология)
In this review, the reasons for successful transplantation of stem cells have been shidied. Special attention has been paid to the influence of some stem cells types on thr immune system, mainly, on activated T-lymphocytes. It has been shown, that mesenchymal and stromal stem cells in vitro blocked the production of T-lymphocytes activated by allogenic cells or non-specific mitogens. Thus, contact with stem cells can impede the development of the graft immunity and inhibit the development of new T-lymphocyte clones. After the immunosuppressive therapy and stem transplantation of CD4+ population, as well as the impediment of the restoration of T-lymphocyte repertoire are observed. This effect is probably connected with immunomodulatory (similar to immunoregulatory) capacity of transferred allogenic or autologous stem cells. These studies have shown the risk of immunosuppression connected with the application of stem cells.